Pharmacokinetics of a potential antiepileptic drug GIZh-298 - G. B. Kolyvanov; A. A. Litvin; O. Yu. Kravtsova; O. G. Gribakina; V. P. Zherdev (Фармакокинетика и Фармакодинамика, 2024)
GIZh-298 pharmacokinetics was studied in rats after different dosage regimens.The aim of this study was to study GIZh-298 pharmacokinetics after its multiple intragastric administration.Methods. The study was conducted on outbred male rats. The concentrations of GIZh-298 in the blood plasma were determined by HPLC with mass-spectrometric detection. Pharmacokinetic parameters were evaluated using a model-independent method.Results. After single and multiple (4 times with a dosage interval of 3 hours) intragastric administrations at 60 mg/kg dose, the test substance in the blood plasma was determined for 4 hours. The mode of administration of GIZh-298 did not affect the value of its half-life and the mean residence time. It has been established that GIZh-298 accumulates in the rats.